Avoidable Utilization of the Chest Pain Observation Unit: Evaluation of Very-Low-Risk Patients - Mahler, Simon A. (Crit Pathw Cardiol, 2013)
BACKGROUND: Very-low-risk patients treated in a chest pain observation unit (CPOU) may threaten efficient care delivery. To optimize the efficiency of CPOU evaluations, it is necessary to quantify the avoidable CPOU utilization rate, examine physician variability, and determine patient and physician characteristics associated with avoidable CPOU utilization. METHODS: Consecutive chest pain patients were evaluated in an Emergency Department-based CPOU. Patients were risk stratified based on the American College of Cardiology/American Heart Association framework, age, and electrocardiogram findings. Very-low-risk was defined as age <35, physician assessment of low-risk, and normal or nondiagnostic electrocardiogram. Patients identified as very-low-risk were considered avoidable CPOU evaluations. Individual physicians’ avoidable CPOU utilization rates were calculated. Patients were followed for 30-day major adverse cardiac events, defined as the composite of death, acute myocardial infarction, and coronary revascularization. RESULTS: Over 33 months, the registry included 1731 chest pain patients. The study definition of avoidable CPOU evaluations was met by 174 patients (10.1%, 95% confidence interval: 8.7–11.6%). The median rate of physician’s avoidable CPOU utilization was 10% (interquartile range: 5.9–13.6%) and varied from 1.9% to 18.4%. None of the patients with an avoidable CPOU evaluation had a major adverse cardiac events within 30 days. Physician predictors of avoidable CPOU utilization included recent residency graduation (<5 years), part-time status, and moderate or high rates of CPOU use. CONCLUSIONS: Approximately 10% of CPOU evaluations were avoidable. Wide variability exists among physicians regarding their individual rates of avoidable CPOU utilization. This variability could represent an opportunity to improve the efficiency of CPOU care delivery.